1998
DOI: 10.1053/euhj.1998.1043
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) as a risk predictor for cardiac mortality in patients with acute coronary syndromes

Abstract: Aims Raised lipoprotein(a) concentrations are considered to be a risk factor for atherothrombotic diseases. We examined whether baseline concentrations were a risk factor for an adverse outcome in patients admitted with acute coronary syndromes. Methods and ResultsFive hundred and nineteen patients admitted with suspected acute coronary syndromes were studied and followed prospectively for a median of 3 years. The prognostic significance of a baseline lipoprotein(a) concentration of d30 mg . dl 1 or lower for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 66 publications
0
45
0
2
Order By: Relevance
“…Another study investigated cardiac mortality in patients with acute coronary syndrome and found a 62% increase in risk with Lp(a) of >30 mg/dL. 26 In the population-based ARIC study (Atherosclerosis Risk in Communities), patients with known cardiovascular disease and elevated Lp(a) levels had an increased risk of recurrent events including MI and stroke. In multivariate analysis, however, Lp(a) remained a significant risk factor for CHD recurrence, but not for the composite end point of CHD and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated cardiac mortality in patients with acute coronary syndrome and found a 62% increase in risk with Lp(a) of >30 mg/dL. 26 In the population-based ARIC study (Atherosclerosis Risk in Communities), patients with known cardiovascular disease and elevated Lp(a) levels had an increased risk of recurrent events including MI and stroke. In multivariate analysis, however, Lp(a) remained a significant risk factor for CHD recurrence, but not for the composite end point of CHD and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…We also found poor outcome in patients with high lipoprotein (a) [5,6,7]. Our other anxiety is about the use of statins in primary prevention, as we have observed serious side effects of these drugs, which not only leach lipid from fatty arterial lesions but also from normal cell membranes, leading to muscular and neurological defects.…”
Section: Beforementioning
confidence: 95%
“…15 In a small study of patients with ACS followed for a median of 3 years, high Lp(a) levels predicted cardiac death. 16 The utility of Lp(a) in predicting events after ACS needs to be assessed in larger studies and needs to be shown to be superior to other variables before it is adopted for clinical use. Lp(a) is attractive because it is actionable; specifically, PCSK9 inhibitors reduce Lp(a) levels by up to 30%.…”
Section: Other Potentially Useful Biomarkers In Acsmentioning
confidence: 99%